Association of prognostic nutritional index with the presence and all-cause mortality of rheumatoid arthritis: the National Health and Nutrition Examination Survey 2003-2018 - Junjie Wang; Rui Zhu; Haonan Fang; Xing Xing; Liru Ge; Guoqi Cai (BMC, 2024)
Abstract Background The prognostic nutritional index (PNI) is a comprehensive measure of individual immune and nutritional status. This study aimed to evaluate the role of PNI in the presence and mortality of rheumatoid arthritis (RA). Methods This study used data of participants aged ≥ 40 years from the National Health and Nutrition Examination Survey (NHANES) 2003-2018. PNI was calculated using serum albumin and lymphocyte count. The relationship between PNI and the prevalence of RA and mortality among RA patients was assessed using logistic and Cox regression models. Nonlinear associations were explored using restricted cubic splines (RCS). Results Of 18,245 participants (mean 55.4 years, 49% female), 1901 had RA, among whom (480/1899, 25%) died during a median follow-up period of 84 months. PNI was inversely associated with the likelihood of having RA (odds ratio = 0.97, 95% confidence interval [CI]: 0.95-0.98). Compared to participants whose PNI was in the lowest quartile, those in other quartiles had a reduced likelihood of having RA by 21-38% (P trend <0.01). Cox regression analysis revealed an inverse association between PNI and all-cause mortality (hazard ratio = 0.95, 95%CI: 0.91-0.99). An L-shaped association was observed between PNI and the presence and all-cause mortality of RA, with turning points occurring around the mean value of PNI. The presence and all-cause mortality of RA was significantly reduced before the turning points of PNI and plateaued afterwards. Conclusion In middle-aged and older adults, there is an inverse association between PNI and the presence and all-cause mortality of RA.